Analysis of the most popular libraries and platforms that can be used to create a model for the intelligent recognition of microfossils (Geo-Eco-Marina, 2022)
This paper presents an analysis of the most common software tools (libraries and platforms) used in the field on AI image processing by building deep learning models. The most useful characteristics for each tool are analyzed for providing a suitable candidate for a deep learning model in the field of intelligent image recognition for microfossils.
Keywords: machine learning; image recognition; microfossils